The thematic constants of prison and family in César Vallejo’s collection of poems Trilce (1922) - Távara Córdova, Francisco (2023)
The centenary of the publication of César Vallejo’s Trilce (1922) merits an examination of the topics that organise the universe of its significance. This research article focuses its attention on the explanation of two fundamental topics: the figuration of the mother (the family centred on her presence and the rituals that revolve around her) and the representation of prison. For the development of the reflections on the first topic, poems XXIII and XXVIII are taken as the object of study, and for the second, poems XXII, XVIII-LVIII and L. The analysis will allow us to understand that the elements that allude to the family universe model a sort of maternalisation of the world; a poetic construction where the presence of the mother is a capital figure, energy and a force that produces meaning, and her absence marks the experience of life as traumatic and empty. Precisely because of this, the experience of prison that some poems communicate, the day-to-day life behind bars, becomes a survivable experience thanks to the memories provided by the maternalisation of the maternal world.